I, Michael Bennett [compact disc, unabridged] - Patterson, James, 1947- (Patterson, James, 1947- Michael Bennett series., 2012)
A South American crime lord has brought New York the worst lawlessness and violence the city has ever seen. Police shot in the street. Judges murdered in the courtroom. Mayhem is unleashed--and the mayor demands that Detective Michael Bennett find a way to stop it. Bennett takes his ten kids and their beautiful nanny, Mary Catherine, out of the chaos on a much-needed vacation to upstate New York. But instead of escaping the violence, it follows them and they find themselves in the middle of another nightmare that threatens the entire family. The danger isn't only coming from the crime lord's killers--FBI Agent Emily Parker is back, and Bennett's attraction to her endangers his relationship with Mary Catherine. A no-holds-barred, pedal-to-the-floor, action-packed audiobook, I, MICHAEL BENNETT is James Patterson at his most thrilling best.